A biomimetic 2D transistor for audiomorphic computing - Sarbashis Das (Nature Portfolio, 2019)
Biomimetic audiomorphic functionalities can be implemented in solid-state devices including 2D materials. Here, the authors fabricate a device based on multiple split gates with nano-gaps on a single semiconducting MoS2 channel that captures the neurobiological architecture and computational map inside the auditory cortex of barn owl.